Kompromi sebagai Kunci Budaya Demokrasi - irena novarlia (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
This article aims to examine the compromise as a key democratic culture. When, tolerance and freedom excluded from the mechanism of the social system, not only makes the further democratic culture of social authority, but social change will be very few are friendly and do not give hope for avoiding conflict. Compromise is the best way and elegant in resolving differences in the interests of democratic culture because it upholds equality, maintaining the balance between rights and obligations, cultivate the attitude of prudence and justice, familiarize consensus in decision making as well as promoting unity and national unity. Compromise as a key democratic culture is an expression of political intelligence without the interests of the group to achieve stability. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2820